Pancasila, Human Rights, and Global Ideology: The Perspective of Human Rights Based on Pancasila in the Midst of the Global Human Rights Wave (Law Research Review Quarterly, 2016)
The view of human rights prevailing in Indonesia in particular has been widely adopted from international human rights principles from various international conventions and treaties. In fact, the principles of human rights that exist so far cannot be denied is very thick in western values: individualism, liberalism and secularism. Meanwhile, Pancasila does not provide room for individualism, liberalism, or secularism. Thus, there is often a conflict of values between international human rights with local human rights values of Pancasila in Indonesia. This paper discusses and analyzes the conflict between international human rights law and human rights principles applied in Indonesia.